The Organizational Resources and Knowledge Management Capability: A Systematic Review - Al Amiri N.; Rahim R.E.A.; Ahmed G. (World Scientific, 2024)
Competitive advantage and sustainability of business organizations can only be achieved when an organization identifies, boosts, and directs its resources toward building its capabilities. The literature identified knowledge management (KM) resources and capabilities as the most critical enablers of organizational performance and innovations. This systematic review identified KM resources (enablers) and their effects on KM capabilities. The review also went into the theories used in the empirical research on the problem. To achieve those goals, the authors summarized 27 quantitative, peer-reviewed studies found in well-known databases and published in the last 5 years between January 2014 and April 2019. The review revealed that the primary organizational KM resources are culture, people, leadership, organization structure, resources, capabilities, strategy and technology. To these, the review added some factors, which are social factors, organizational knowledge and organizational characteristics. The study is significant in finding the most common variables or factors in business KM and their implication of them for enhancing knowledge capability and organizational performance. 2023 World Scientific Publishing Co.